2021
DOI: 10.15244/pjoes/122449
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lead (II) Removal from Wastewater Using Banana Peels: Optimization Study

Abstract: The response surface methodology was used to investigate the removal of Pb (II) from an aqueous solution using banana peel with varying operating parameters in a batch mode. The central composite design was used to study the interactive effects of the operating parameters (initial concentration, pH of the solution, adsorbent dosage and the particle size). The banana peel was characterized by FTIR which showed the functional groups, while SEM and EDS were used to study morphology and elemental composition. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…Our results are comparable to those reported in the literature for optimal Pb(II) adsorption conditions (pH range between 4 and 6) determined for organic residues such as the carnauba palm (Oliveira et al 2021), banana peel (Afolabi et al 2021), tomato residues (Heraldy et al 2018), and particularly coffee husk and pulp residues (Zaragoza et al 2011) where at pH = 4.25 almost 100% of Pb is removed from solution.…”
Section: Biosorbent Properties Ph Effectsupporting
confidence: 90%
“…Our results are comparable to those reported in the literature for optimal Pb(II) adsorption conditions (pH range between 4 and 6) determined for organic residues such as the carnauba palm (Oliveira et al 2021), banana peel (Afolabi et al 2021), tomato residues (Heraldy et al 2018), and particularly coffee husk and pulp residues (Zaragoza et al 2011) where at pH = 4.25 almost 100% of Pb is removed from solution.…”
Section: Biosorbent Properties Ph Effectsupporting
confidence: 90%
“…On the other hand, lead, a reasonably malleable corrosion-resistant metal, because it melts quickly, has several uses, and is expected mainly in paints and toxic fumes from industries such as metallurgy, mining and construction industries [ 113 ]. It has been shown that through the use of banana peel, removal efficiencies of up to 98% can be achieved with initial concentrations of 100 mg/L, pH 5.0, the adsorbent dosage of 0.55 g and particle size of 75 μm [ 114 ].…”
Section: Use Of Banana Waste-lossmentioning
confidence: 99%
“…In fact, a large number of reported studies have been conducted to valorize biomasses as sorbents for heavy metal species from aqueous solutions such as olive stones from olive meal waste waters and apricot shells waste from fruit juice industry, which are potential sorbents for several metal ions [18][19]. Moreover, various plant peels have been used efficiently in the adsorption of different metals such as lead on potato and banana peels [20][21]. Finally, a previous study established that Nigella sativa L. seeds biomass preliminarily defatted as a potential sorbent for lead from aqueous solutions and wastewaters from battery factories [22].…”
Section: Introductionmentioning
confidence: 99%